The influence of managerial attention on the deployment of dynamic capability: a case study of Internet platform firms in China. (28th December 2018) - Zeng, Jing; Mackay, David
Abstract: We examine the interaction of processes of managerial attention and dynamic capabilities deployment, drawing on qualitative data from the development of two Internet platform companies—Alibaba and Tencent—over their first 15 years of existence. Informed by senior management interviews, we create a process model of the relationship between activities of managerial attention and dynamic capability deployment within context. We show how the focus of managerial attention on aspects of the organizational context leads to the deployment of specific dynamic capabilities. Further, we propose that a continuing focus of managerial attention to any aspect of the organization's context gives rise to core dynamic capabilities—a set of continually deployed processes for changing the resource base in a way that corresponds with the strategic logic of the organization. We find that core dynamic capabilities are complemented by contingent dynamic capabilities—intermittently deployed strategic change processes that enable and enhance the use of core dynamic capabilities.